Functional Connectivity Dynamics Altered of the Resting Brain in Subjective Cognitive Decline - Wei, Yi-Chia; Kung, Yi-Chia; Huang, Wen-Yi; Lin, Chemin; Chen, Yao-Liang; Chen, Chih-Ken; Shyu, Yu-Chiau; Lin, Ching-Po (Frontiers in Aging Neuroscience, 2022)
Background: Subjective cognitive decline (SCD) appears in the preclinical stage of the Alzheimer’s disease continuum. In this stage, dynamic features are more sensitive than static features to reflect early subtle changes of functional brain connectivity. Therefore, we studied local and extended dynamic connectivity of the resting brain of people with SCD to determine their intrinsic brain changes. Methods: We enrolled cognitively normal older adults from the communities and divided them into SCD and normal control (NC) groups. We used the mean dynamic amplitude of low-frequency fluctuation (mdALFF) to evaluate the region of interest (ROI)-wise local dynamic connectivity of resting-state functional MRI. The dynamic functional connectivity (dFC) between ROIs was tested by whole brain-based statistics. Results: When comparing SCD (N=40) with NC (N=45), mdALFFmean decreased at right inferior parietal lobule (IPL) of the frontoparietal network (FPN). Still, it increased at the right middle temporal gyrus (MTG) of the ventral attention network (VAN) and right calcarine of the visual network (VIS). Also, the mdALFFvar (variance) increased at the left superior temporal gyrus of AUD, right MTG of VAN, right globus pallidum of the cingulo-opercular network (CON), and right lingual gyrus of VIS. Furthermore, mdALFFmean at right IPL of FPN correlated negatively to subjective complaints and positively to objective cognitive performance. In the dFC seeded from the ROIs with local mdALFF group differences, SCD showed a generally lower dFCmean and higher dFCvar (variance) to other regions of the brain. These weakened and unstable functional connectivity appeared among FPN, CON, the default mode network, and the salience network, the large-scale networks of the triple network model for organizing neural resource allocations. Conclusion: The local dynamic connectivity of SCD decreased in brain regions of cognitive executive control. Meanwhile, compensatory visual efforts and bottom-up attention rose. Mixed decrease and compensatory increase of dynamics of intrinsic brain activity suggest the transitional nature of SCD. The FPN local dynamics balance subjective and objective cognition and maintain cognitive preservation in preclinical dementia. Aberrant triple network model features the dFC alternations of SCD. Finally, the right lateralization phenomenon emerged early since the SCD stage and affected local dynamic connectivity.